Endoscopy by Nonphysicians - Elaine R Gossman (Canadian Journal of Gastroenterology)
In 1945, Henry J Kaiser organized a group of physicians to provide health care for shipyard workers and their families. His foundation, Kaiser Permanente (USA), has developed into a prepaid health plan facility serving 8.4 million members in nine states and in Washington, DC, within the United States. It aspires to provide high quality, affordable, integrated health care within an organized, efficient system. A focus on preventive care in a cost-effective manner is a high priority. The Kaiser Permanente northwest region (covering northwest Oregon and southwest Washington) serves nearly one-half of a million members. Our region has utilized nurse practitioners (NPs) and physician assistants (PAs) (allied health care providers) in a variety of capacities for many years. The present paper reviews the background and current status of their role in endoscopy.